Minimally Invasive Resection of Benign Gastric Tumors in Challenging Locations: Prepyloric Region or Gastroesophageal Junction. Issue 10 (October 2013) - Armstrong, Christopher; Gebhart, Alana; Smith, Brian R.; Nguyen, Ninh T.
Benign gastric tumors in a prepyloric location or within 3 cm adjacent of the gastroesophageal junction (GEJ) are often challenging to resect using minimally invasive surgical techniques. The aim of this study was to examine the outcomes of patients who underwent minimally invasive enucleation or resection of benign gastric tumors at these difficult locations. The charts of patients undergoing minimally invasive resection of benign-appearing submucosal gastric tumors between June 2001 and December 2012 were reviewed. Data on tumor size and location, type of minimally invasive surgical resection, perioperative complications, 90-day mortality, pathology, and recurrence were collected. A total of 70 consecutive patients underwent laparoscopic resection of benign-appearing submucosal gastric tumors; there were 24 patients with lesions close to the GEJ and nine patients with lesions close to the prepyloric region. All lesions were successfully resected laparoscopically. For prepyloric tumors, surgical approaches included enucleation (n = 1), wedge resection (n = 2), and distal gastrectomy with reconstruction (n = 6). For tumors close to the GEJ, surgical approaches included enucleation (n = 16), wedge resection (n = 3), and esophagogastrectomy (n = 5). Complications in this series of 33 patients included late strictures requiring endoscopic dilation in three patients who underwent esophagogastrectomy. The 90-day mortality rate was zero. There were no recurrences over a mean follow-up of 15 months (range, 1 to 86 months). Minimally invasive enucleation or formal anatomic resection of submucosal tumors located adjacent to the GEJ or at the prepyloric region is safe and carries a low risk for tumor recurrence. Submucosal gastric lesions adjacent to the GEJ are amenable to laparoscopic enucleation or wedge resection unless they extend proximally into the esophagus. Prepyloric lesions often require formal anatomic resection with reconstruction.